Gastroprotective activity and mechanisms of action of Bauhinia purpurea Linn (Leguminoseae) leaf methanol extract - Kamarolzaman, M. F. F.; Yahya, F.; Mamet, S. S.; Jakius, K. F.; Mahmood, N. D.; Shahril, M. S.; Mohtarrudin, N.; Suhaili, Z.; Zakaria, Z. A. (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2014)
Purpose: To determine the gastroprotective activity and mechanisms of protection of the methanol extract of Bauhinia purpurea leaves (MEBP) using ethanol-induced gastric ulcer model. Methods: Male Sprague Dawley rats (n = 6) were administered orally with 10 % DMSO, 100 mg/kg ranitidine or MEBP (50, 250 and 500 mg / kg) daily for 7 consecutive days prior to subjection to the ethanol-induced gastric ulcer assay. The mechanisms of gastroprotection were determined based on: i) antisecretory activity via pylorus ligation assay; ii) the role of nitric oxide (NO) and sulfhydryl group via pre-treatment of MEBP-treated rats with the respective N-nitro-L-arginine methyl ester (L-NAME) or carbenoxolone (CBX) followed by the ethanol-induced assay; and iii) antioxidant activity using superoxide anion radical scavenging assay and, oxygen radical absorbance capacity (ORAC) assay. Ranitidine (100 mg / kg) was used as the reference drug. . Results: MEBP exhibited a significant (p < 0.05) and dose-dependent gastroprotective activity against ethanol-induced gastric ulcer with ulcer formation ranging between 0 and 74 % (indicated by decrease in ulcer area from 21.3 to 5.5 mm2). The macroscopic observation was in line with the microscopic findings and further supported by the histological scores suggesting the antiulcer potential of MEBP. MEBP also significantly (p < 0.05) reduced volume gastric juice, as well as its free and total acidity while increasing its pH. Moreover, this activity was significantly (p < 0.05) modulated in the presence ofsulfhydryl group, but not NO. The extract also exhibited significant (p < 0.05) antioxidant activity. Conclusion: MEBP exerts gastroprotective activity partly via its antisecretory and antioxidant activities, as well as by modulation of sulfhydryl group, but not NO action.